Influence of Pricing Strategy on Brand Image and Willingness to Pay in Indonesia's Premium Furniture, Case Study: PT. Caledon Design Center - Siswi Andini (Journal of World Science, 2025)
This research examines how pricing strategies impact on brand image and willingness to pay. The author uses the sofa as major contributor to business and chooses the top five sofa types with Marvin, Evita, Leo, Korus, and Dallas. The study addresses three research questions (1) What is the effective pricing strategy based on PED analysis? (2) Does pricing strategy have an impact on customer willingness to pay? And (3) How does Caledon’s pricing strategy affect its premium brand image?. Triangulation analysis across three methodologies, Price Elasticity of Demand (PED) using transactional data from December 2023 to July 2025, PLS-SEM with survey data from 140 respondents, and descriptive analysis of customer demographics and behavior, strongly supports the development of robust business case solution. Integrated results demonstrate that pricing strategies effectively segment products under PED analysis. However, the connection between pricing strategy and willingness to pay is weak, with a p-value 0,065 and T-statistics 1.847, higher than T-table value of 1.657. Similarly, the relationship of brand image to willingness to pay was also rejected with a p-value 0,114 and 1.581 T-statistics. Only tpricing strategy has a positive effect on brand image with Path Coefficient = 0.839, T-statistics = 35.610, and p-values <0.001. This mark that pricing strategy powerfully signals only for building brand image perceptions, without directly influencing willingness to pay